2016
DOI: 10.1186/s12879-016-1678-9
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of invasive Acinetobacter species isolates recovered in a pediatric academic center

Abstract: BackgroundAcinetobacter species are associated with increasing mortality due to emerging drug-resistance. Pediatric Acinetobacter infections are largely undefined in developed countries and clinical laboratory identification methods do not reliably differentiate between members of the Acinetobacter calcoaceticus-baumannii complex, leading to improper identification. Therefore we aimed to determine risk factors for invasive Acinetobacter infections within an academic, pediatric setting as well as defining micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
(33 reference statements)
1
8
0
Order By: Relevance
“…If so, should we expect worse clinical outcomes upon the acquisition of resistance by these Acinetobacter species? Under this assumption, A. nosocomialis and A. baumannii might have suffered a reduction of intra-species diversity (population bottleneck) resulting from adaptation to the human host and/or antibiotic selection, while the variability observed among isolates of A. pittii , A. seifertii and A. lactucae might reflect their emergence and distinct degrees of adaptation as human nosocomial pathogens (Schleicher et al, 2013; Jain et al, 2016; Chen et al, 2018; Pailhories et al, 2018; Rocha et al, 2018). Nevertheless, it is important to acknowledge that the results provided in our study arise from the usage of in vitro and nematode infection models that do not entirely reflect more complex clinical scenarios and, thus, the extrapolation of these results to infer virulence in the human host must be taken with extreme caution.…”
Section: Discussionmentioning
confidence: 99%
“…If so, should we expect worse clinical outcomes upon the acquisition of resistance by these Acinetobacter species? Under this assumption, A. nosocomialis and A. baumannii might have suffered a reduction of intra-species diversity (population bottleneck) resulting from adaptation to the human host and/or antibiotic selection, while the variability observed among isolates of A. pittii , A. seifertii and A. lactucae might reflect their emergence and distinct degrees of adaptation as human nosocomial pathogens (Schleicher et al, 2013; Jain et al, 2016; Chen et al, 2018; Pailhories et al, 2018; Rocha et al, 2018). Nevertheless, it is important to acknowledge that the results provided in our study arise from the usage of in vitro and nematode infection models that do not entirely reflect more complex clinical scenarios and, thus, the extrapolation of these results to infer virulence in the human host must be taken with extreme caution.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted on 48 Acinetobacter isolates from bacteremia patients demonstrated that A. soli was the most prevalent species in a tertiary hospital setting in Japan (15). Moreover, according to another report (16), the most frequently isolated Acinetobacter species in a pediatric academic center in the U.S. was A. pittii, which accounted for 45.8 of the total number. Importantly, the authors observed significantly higher biofilm formation capabilities by A. pittii than other strains, including A. baumannii, highlighting the importance of being able to discriminate among Acinetobacter species.…”
Section: Discussionmentioning
confidence: 98%
“…Acinetobacter species were found to be associated with increased mortality [9]. The ACB complex has emerged as a high priority nosocomial pathogen, especially in intensive care units, thereby posing a challenge to infection management practices [10].…”
mentioning
confidence: 99%
“…However, identification of Acinetobacter to the species level remains complicated. Clear differentiation among various Acinetobacter species using standard biochemical methods and automated systems are challenging, thus leading to inaccurate identification [9]. Although various molecular methods are available, they are not regularly employed in routine diagnostic laboratories [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation